Potential of «universal» bonding agents for composite repair. Issue 1 (31st December 2022) - Staxrud, Frode; Valen, Håkon
Abstract: Aim: The aim of this in vitro study was to compare nine different bonding agents of so-called universal type with one well-recognized, 3-step etch-and-rinse bonding agent, as control, in a composite-to-composite shear bond strength (SBS) test. Materials and methods: Cylindrical composite substrates were made according to manufacturers' specifications and potted in epoxy according to the description in ISO TS 29022:2003. They were stored in water (37 °C) for 2 months (for water sorption). New composite was bonded to the substrates using nine different bonding agents of universal type, and one 3-step etch-and-rinse bonding agent as control. Fifteen specimens were made for each bonding agent as required by ISO 29022. SBS testing was performed as described in the standard. Vertical load was applied at the speed of 1 mm/min, using a universal testing machine. Two test series were performed: (A) Short term test of SBS after 2 weeks (B) Long term test of SBS after 1-year storage of specimens in water at 37 °C. Results: Test results for the short term test (A); composite-to-composite SBS mean values ranged from 12.0 to 24.9 MPa, and for the long term test (B), SBS ranged from 11.4 to 25 MPa. Six universal bonding agents showed significantly higher bond strength than control in 1-year test. Conclusion: In this in vitro study, testing shear bond strength of composite-to-composite bonding, the universal bonding agents performed similar and for some agents better than the 3-step etch-and-rinse bonding agent. New simplified bonding procedures seem reliable for repair of composite.